Ferroptosis-based advanced therapies as treatment approaches for metabolic and cardiovascular diseases - Maremonti, Francesca; Tonnus, Wulf; Gavali, Shubhangi; Bornstein, Stefan; Shah, Ajay; Giacca, Mauro; Linkermann, Andreas Günter (Cell death and differentiation, 2024)
Ferroptosis has attracted attention throughout the last decade because of its tremendous clinical importance. Here, we review the rapidly growing body of literature on how inhibition of ferroptosis may be harnessed for the treatment of common diseases, and we focus on metabolic and cardiovascular unmet medical needs. We introduce four classes of preclinically established ferroptosis inhibitors (ferrostatins) such as iron chelators, radical trapping agents that function in the cytoplasmic compartment, lipophilic radical trapping antioxidants and ninjurin-1 (NINJ1) specific monoclonal antibodies. In contrast to ferroptosis inducers that cause serious untoward effects such as acute kidney tubular necrosis, the side effect profile of ferrostatins appears to be limited. We also consider ferroptosis as a potential side effect itself when several advanced therapies harnessing small-interfering RNA (siRNA)-based treatment approaches are tested. Importantly, clinical trial design is impeded by the lack of an appropriate biomarker for ferroptosis detection in serum samples or tissue biopsies. However, we discuss favorable clinical scenarios suited for the design of anti-ferroptosis clinical trials to test such first-in-class compounds. We conclude that targeting ferroptosis exhibits outstanding treatment options for metabolic and cardiovascular diseases, but we have only begun to translate this knowledge into clinically relevant applications.
Online veröffentlicht: 27. Juli 2024
Gesehen am 28.10.2024